THE EFFECT OF RAW MATERIAL PURCHASE COSTS AND LABOR COSTS ON OPERATIONAL PROFITS OF KEDAI SADJIWA BANTEN - Adiansyah, Gressita Melani; Hernawati, Euis (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research was employed using a quantitative method. The main objective of the researchis has a purpose to analyze the budget for purchasing raw materials and the budget for laboron operating profits at Kedai Sadjiwa. The data of the research were important informationsourced from companies and staff who work at Kedai Sadjiwa. The data comes fromcollection methods which on the job training, observations, and literature studies. The dataused is the financial report of Kedai Sadjiwa for the 2016-2020 period. The data is processedusing the IBM SPSS statistics subscription version 26.0. The data analysis were used are theclassical assumption test in the form of normality test, multicollinearity test,heteroscedasticity test, autocorrelation test, multiple linear regression analysis, coefficientof determination hypothesis test, f test and t test. The results of the research found thatsegmentally the cost of purchasing raw materials had a significant impact on operating profitwith a significance of 0.022 <0.05. Labor costs have a significant effect on operating profitwith a significance of 0.013 < 0.05. It is known that the raw material purchase budget andthe labor budget simultaneously have a significant impact on operating profit with asignificance of 0.026 < 0.05.